Only time will tell - Archer, Jeffrey, 1940- (Archer, Jeffrey, 1940- Clifton chronicles, 2012)
Harry Clifton, having been raised by his uncle who was a shipyard worker, finds the expectations for his life changing after winning a scholarship to a prestigious boys' school, finding out the truth about his father's death, and questioning his lineage.